ASPEK DIKSI SERTA NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL AYAH KARYA ANDREA HIRATA - Rizqi, Annis Kurniyati; Suwandi, Sarwiji; Suhita, Raheni (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This study aimed to describe and explain: (1) the aspects of diction used in the novel Ayah by Andrea Hirata; (2) the values of character education in the novel Ayah by Andrea Hirata; and (3) the relevance of Andrea Hirata’s novel Ayah as a teaching material of language and literature in Vocational High School. This study is a qualitative research that analyzes the data in the form of documents with the object of study of novel Ayah by Andrea Hirata. The results of this study are as follows. (1) The diction aspect contained in Andrea Hirata's father's novel includes five types of diction, (2) Novels contain sixteen points of character education values, (3) Novel Ayah is relevant to the learning of Indonesian language and literature in SMK because the aspect of diction and the value of character education in accordance with the learning objectives that have been designed using the Learning Implementation Plan based on the Core Competence and Basic Competence which includes the competencies that the learners must achieve in language and literature learning. Dad's novel can increase students' vocabulary mastery according to language ability, student psychology, and cultural background.